Proteomic insights into intra- and intercellular plant-bacteria symbiotic association during root nodule formation - Salavati, Afshin; Shafeinia, Alireza; Klubicová, Katarína; Bushehri, Ali Akbar Shahnejat; Komatsu, Setsuko (Frontiers in Plant Science, 2013)
Over the last several decades, there have been a large number of studies done on the all aspects of legumes and bacteria which participate in nitrogen-fixing symbiosis. The analysis of legume-bacteria interaction is not just a matter of numerical complexity in terms of variants of gene products that can arise from a single gene. Bacteria regulate their quorum-sensing genes to enhance their ability to induce conjugation of plasmids and symbiotic islands, and various protein secretion mechanisms; that can stimulate a collection of chain reactions including species-specific combinations of plant-secretion isoflavonoids, complicated calcium signaling pathways and autoregulation of nodulation mechanisms. Quorum-sensing systems are introduced by the intra- and intercellular organization of gene products lead to protein–protein interactions or targeting of proteins to specific cellular structures. In this study, an attempt has been made to review significant contributions related to nodule formation and development and their impacts on cell proteome for better understanding of plant-bacterium interaction mechanism at protein level. This review would not only provide new insights into the plant-bacteria symbiosis response mechanisms but would also highlights the importance of studying changes in protein abundance inside and outside of cells in response to symbiosis. Furthermore, the application to agriculture programe of plant-bacteria interaction will be discussed.